Adverse Childhood Experiences, Coping Strategies, and Emotional Distress on Young Adults During the COVID-19 Pandemic: [Pengalaman Buruk di Masa Kecil, Strategi Coping, dan Hendaya Emosional Pada Individu Dewasa Muda Selama Pandemi COVID-19] - Shanen Emily; Dewi, Zahrasari Lukita (Faculty of Psychology, Universitas Surabaya, 2023)
The purpose of this study was to examine the relationship between adverse childhood experiences and the use of coping strategies on the emergence of emotional distress in young adults during the COVID-19 pandemic. A number of previous studies found an increase in emotional distress in young adults the COVID-19 pandemic. The authors suspect that there is a role of adverse childhood experiences and the use of maladaptive coping strategies on emotional distress during the COVID-19 pandemic. This study utilizes quantitative method with three measuring instruments, namely: (1) Adverse Childhood Experiences (ACEs); (2) Depression, Anxiety, and Stress 42 (DASS-42); and (3) Ways of Coping Scale (WCS). The participants of this study were 278 young adults, whom had at least one adverse childhood experience, and lives in the Jabodetabek area. The results showed that there was a positive correlation between emotional distress and adverse childhood experiences and emotion-focused coping strategies. In addition, emotional distress also has a negative correlation with problem-focused coping strategies. Considering the results of this study, the treatment that needs to be given to young adults who have emotional distress during the COVID-19 is by strengthening the individual's ability to cope with the problems experienced during the COVID-19 pandemic, and involving the acceptance of adverse childhood experiences. Tujuan studi ini adalah meneliti hubungan antara pengalaman buruk di masa kecil dan penggunaan strategi coping terhadap hendaya emosional pada individu dewasa muda selama pandemi COVID-19. Sejumlah hasil studi sebelumnya menunjukkan peningkatan hendaya emosional yang dialami oleh individu dewasa awal selama pandemi COVID-19. Penulis menduga adanya peranan pengalaman buruk di masa kecil dan strategi coping yang kurang adaptif pada hendaya emosional selama pandemi COVID-19. Studi ini menggunakan metode kuantitatif dengan tiga alat ukur, yaitu: (1) Adverse Childhood Experiences (ACEs); (2) Depression, Anxiety, and Stress 42 (DASS-42); dan (3) Ways of Coping Scale (WCS). Partisipan studi ini berjumlah 278 individu dewasa muda, yang memiliki minimal satu pengalaman buruk di masa kecil, dan berdomisili di area Jabodetabek. Hasil studi menunjukkan adanya hubungan positif antara hendaya emosional dengan pengalaman buruk di masa kecil dan penggunaan strategi coping yang berfokus pada emosi. Selain itu, hendaya emosional juga memiliki hubungan negatif dengan penggunaan strategi coping yang berfokus pada masalah. Mempertimbangkan hasil studi ini, penanganan yang perlu diberikan pada individu dewasa muda dengan hendaya emosional selama pandemi COVID-19 adalah dengan memperkuat kemampuan individu dalam mengatasi masalah yang dialami selama pandemi COVID-19, serta melibatkan penerimaan terhadap pengalaman buruk di masa kecil.